1985
DOI: 10.1136/jcp.38.10.1100
|View full text |Cite
|
Sign up to set email alerts
|

Follicular thyroid tumours: a study of laminin and type IV collagen in basement membrane and endothelium.

Abstract: SUMMARY Immunocytochemical stains for laminin and type IV collagen can be used as markers for basement membrane and vascular endothelium. Thirty four follicular thyroid lesions were examined using these techniques to investigate two aspects: firstly, the relation between the extent of invasion and the integrity of basement membrane; secondly, whether the techniques could enhance the detection of tumour vascular invasion. The results showed that although basement membrane was lost in widely invasive tumours, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 14 publications
(1 reference statement)
1
4
0
Order By: Relevance
“…[42][43][44] To our knowledge, the consistent pericellular laminin deposition in anaplastic carcinomas which we observed in this study has not been previously reported. Although laminin is a natural ligand, we did not find a correlation between galectin-3 immunostaining and laminin expression.…”
Section: Discussionsupporting
confidence: 60%
“…[42][43][44] To our knowledge, the consistent pericellular laminin deposition in anaplastic carcinomas which we observed in this study has not been previously reported. Although laminin is a natural ligand, we did not find a correlation between galectin-3 immunostaining and laminin expression.…”
Section: Discussionsupporting
confidence: 60%
“…2 Recent oncologic literature has stressed the proteolytic action of some enzymes produced by neoplastic cells. 2 Recent oncologic literature has stressed the proteolytic action of some enzymes produced by neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The α2β1 complex is the one with higher upregulation in thyroid carcinomas (up to 9-fold for ITGA2 vs. 2.5-fold for ITGA3 and ITGAV), although it is not the most abundant integrin expressed. This receptor, whose expression in benign and malignant thyroid tumors was previously detected by immunodetection, binds LM, COL, and heparan sulfate proteoglycan core protein, an integral component of the basement membrane [6,33]. Alpha 2β1 is over-expressed in a variety of cancer cells and experimental evidence suggest that its aberrant expression might contribute to invasion, metastasis, and drug resistance in non-small cell lung, ovarian, and breast cancer, pancreatic ductal adenocarcinoma, and hepatocellular carcinoma, being associated with poor survival in pancreatic ductal adenocarcinoma and potential therapeutic target for gastric cancer [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 90%
“…Invasive carcinomas generally show aberrant basement architecture and loss of LM around the epithelial structures [32]. Early thyroid immunohistochemical studies highlighted that adenomas and non-invasive FTC tend to preserve the basement membrane around the follicles while its partial or complete loss can be recognized in widely invasive FTC [33]. In contrast, PTC preserves basement membrane structure with abundant LM around the follicles [31].…”
Section: Discussionmentioning
confidence: 99%